1989
DOI: 10.1056/nejm198912073212302
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori Infection and Histologic Gastritis in Asymptomatic Persons

Abstract: We estimated the prevalences of Helicobacter pylori (formerly called Campylobacter pylori) infection and histologic gastritis in 113 asymptomatic persons, using endoscopic biopsy of the gastric antrum and corpus. Unsuspected lesions, mainly mucosal erosions, were revealed at endoscopy in 16 subjects (14 percent). Gastritis was found in 42 subjects (37 percent), of whom 36 (32 percent of the total) were found to be infected with H. pylori on the basis of hematoxylin-eosin staining. H. pylori was not found in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
332
3
11

Year Published

1990
1990
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 727 publications
(362 citation statements)
references
References 33 publications
16
332
3
11
Order By: Relevance
“…Using data from four studies, Rockey reported that upper gastrointestinal lesions were found in approximately 41% of patients with iron deficiency anemia [16]. However, the 30% prevalence of upper gastrointestinal findings in our study was higher that that found in asymptomatic adults, which is estimated at 14% [17]. The high prevalence of gastrointestinal findings in our study supports our hypothesis that these lesions contributed to iron deficiency in our patients and were not incidental findings.…”
Section: Discussionsupporting
confidence: 76%
“…Using data from four studies, Rockey reported that upper gastrointestinal lesions were found in approximately 41% of patients with iron deficiency anemia [16]. However, the 30% prevalence of upper gastrointestinal findings in our study was higher that that found in asymptomatic adults, which is estimated at 14% [17]. The high prevalence of gastrointestinal findings in our study supports our hypothesis that these lesions contributed to iron deficiency in our patients and were not incidental findings.…”
Section: Discussionsupporting
confidence: 76%
“…The prevalence of infection caused by the H. pylori in Latin America is around 60%, varying from 30% to 90% (5) . H. pylori causes inflammation of the gastric mucosa in all infected individuals (10) . This inflammation consists initially in recruitment of neutrophils, followed by lymphocytes, with later epithelial damage (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the analogy that chronic gastritis usually is a consequence of the presence of overlaying H. pylori in the lumen (27), we examined the distal esophagus to determine whether bacterial cells might be visible. Such a study, if positive, can provide morphological evidence for an indigenous esophageal biota.…”
Section: Microscopic Examination Of Bacterial Biota In the Distal Esomentioning
confidence: 99%